The Protection of the Journalist's Sources - Hovhannisyan, Arpine (Bulletin of Yerevan University C: Jurisprudence, 2023)
The Article is dedicated to the protection of the journalist's sources. It explores the main international tools and documents for protecting journalists' sources. Moreover, the Article observes the protection of the journalist's source from different dimensions: provision of material, requiring a journalist to testify in the court, searches of media organizations, and private homes of journalists' surveillance. Based on the international best practices and decisions of the European Court of Human Rights, the Article provides the main criteria for the protection of the journalist's sources in the Armenian legal framework.
Keywords: Freedom of speech; journalist's sources; journalist; ECHR